Auditoría de cumplimiento y su relación con las obligaciones tributarias de agrocomercio Morejón, cantón El Empalme, año 2012 - Rosales Villigua, Norman Manuel (2015)
This research topic is to develop a compliance audit checking processes, rules and policies in relation to the tax obligations of Agrocommercio Morejon, 2012. The Internal Control is understood as the process running the administration in order to assess specific operations with reasonable safety in three major categories: effectiveness and operational efficiency, reliability of financial reporting and compliance with policies, laws and regulations. This research project detailing the components of internal control that kept the company Agrocommercio Morejon during 2012, and their evaluation by the COSO model I applied to the management of the company studied, showed a confidence level of 87.00% considered, and a risk level of 13.00% establecido.La operational efficiency is closely related to tax compliance maintaining a company within a fiscal year; in the case of agribusiness and Piladora Morejon maintains a positive environment in terms of operational efficiency of the company, as evidenced by the performance indicators and applied management showed a 100% with the statements of SRI, as I show it analyzed and it is recommended to permanently monitor the accounting department so that tax obligations are met efficiently to improve business processes developed by the company during a fiscal year. Standards and tax policies are set by the tax administration through the tax code, the Organic Law on Internal Taxation and Regulations; once evaluated the statements presented by the company in 2012, it was found that the company conducts its statements according to Ecuadorian tax legislation.